الخطاب الكرامي في النص الصوفي وصداه في المخيال الجمعي - بوقعادة, البشير (University of Eloued جامعة الوادي, 2019)
تعالج هذه الورقة البحثية مادة الخطاب الكرامي-الصوفي، الذي شيّد عرشه "محمد الصباغ القلعي في جسم مصنّفه الموسوم بـ "بستان الأزهار في مناقب زمزم الأخيار ومعدن الأنوار سيدي أحمد بن يوسف الراشدي النسب والدار"، حين طرق سيرة الولي "أحمد بن يوسف الملياني"، وما احتفظت به النصوص المصدرية بشأن ترجمته، وذلك من حيث طبيعة ألوان الكرامة ونسيج الخطاب الكرامي الذي تضمّنته سيرة "أحمد بن يوسف الراشدي الملياني"، بما تخلّلها من أشكال للكرامة وصنوفها. كما اضطلعت بتحليل نماذج من ألوان الكرامة التي أوردها صاحب المصنَّف، ومناقشتها، وعرضها على القصاص العقلي والتاريخي، ومناقشة نماذج من مواقف المصنِّف من المادة الكرامية التي تناولها في بحر مؤلفه، كما تتبعت مدى حضور الخطاب الكرامي في السلوك المجتمعي، وتمثّلاته في واقعه، وكذا مستويات وقعه في المخيال الجمعي بالمغرب الأوسط في عصر المؤلف، وفي عصر من أعقبه بناءً على ما احتفظت به المادة المصدرية بشأن كراماته. This research paper aims to investigate the speech of dignity material founded by "Muhammad Al Sabagh Al Qualii " within his Mussanaf (compendium) "Bustan AL Azhar (the garden of flowers) in the virtues of Zamzamthe the righteous and the metal of lights Sidi Ahmed bin Yousef Al Rashidi, the parentage and the house" which has dealt with the life and conduct of AL Wali Al Salih (the good guardian) Sidi Ahmed bin Yousef Al Malyani, and what have been kept within the source texts as far as his biography is concerned. And that is in terms of the nature of dignity kinds and the speech of dignity material contained in the biography of "Ahmed bin Yousef Al Rashidi Al Malyani". It has also carried out an analysis and discussion of some models of the dignity kinds raised by the author of the book and bringing them to the historical and reasonal judgment. In addition, it has discussed other models of the attitudes of the dignity material that have been addressed in the manuscript. The paper has also investigated the influence of the dignity speech on the social behaviour and it's manifestations in reality, and also the levels of its influence on the social perspective in the Middle West in the author's era, and the era of those who came after him based on what the source material has kept as far as his dignity is concerned.
the Speech Of Dignity In The Mystical TextAnd Its Resonance In The Social Perspective : "bustan AlAzhar Manuscript (the Garden Of Flowers) In The Virtues Of
مقال
Keywords: الكرامة ; التصوف ; الخوارق ; الخطاب ; المجتمع ; التمثلات ; المخيال ; Dignity ; Sufism ; mircales ; speech ; society ; manifestations ; perspectiv